Appropriate norms of physical development of student’s youth - Шутєєв, В’ячеслав (Slobozhanskyi Herald of Science and Sport, 2016)
Shuteyev, V. Purpose: the determination of proper norms of physical development of student’s youth. Material & Methods: the following indicators were used for the assessment of physical development of students: body weight, length of body standing, vital capacity of lungs. Index of body weight and vital index were defined on their basis. The selective method was used for the establishment of borders of the confidential interval. Results: the assessment of ratio of weight and length of body at students and students, who participated in the research, showed that it is in norm limits, and the size of vital index is lower than norm. Conclusions: results of the carried-out analysis showed that the level of physical development of students of NLA and KhHPA meets the established standards and the relevant data which are submitted in special literature. The borders of the confidential interval are established for indicators of physical development of students on the basis of the obtained data which characterize the general population.